The mutagenic effects of pesticides on enteric bacterial pathogens: a scoping review - Hoque, Ashna Ambrin (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2022.